1988
DOI: 10.1007/bf01805842
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant trial for stage II receptor-positive breast cancer: CMF vs. CMF+ tamoxifen in a single centre

Abstract: The purpose of a randomized trial achieved in a single centre (Fondation Bergonié, Bordeaux, France) was to compare chemotherapy alone (intravenous CMF) versus chemotherapy and hormonotherapy (CMF plus tamoxifen-30 mg per day during 2 years), for patients with stage II breast carcinoma and positive values of estrogen and/or progesterone receptor (EPR) (greater than 10 and greater than 15 fmoles mg protein-1 respectively). Three hundred and thirty four women treated by surgery +/- radiotherapy are included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
1
8
0
1
Order By: Relevance
“…There was no difference between the groups in terms of incidence of changes in leucocyte counts, impaired liver function, pigmentation, etc., suggesting no potentiation of adverse effects by addition of TAM to FT (Table VI). tulated that there would be a greater advantage from TAM in a group with tumours 3 cm or larger in size than those with tumours less than 3 cm in size (Mauriac et al, 1988). This study was performed as a part of nationwide Japanese trials on post-operative adjuvant chemo-endocrine therapy for stage II and stage IIIa breast cancer with ftorafur (FT) alone and FT plus tamoxifen (TAM) and six districts.…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference between the groups in terms of incidence of changes in leucocyte counts, impaired liver function, pigmentation, etc., suggesting no potentiation of adverse effects by addition of TAM to FT (Table VI). tulated that there would be a greater advantage from TAM in a group with tumours 3 cm or larger in size than those with tumours less than 3 cm in size (Mauriac et al, 1988). This study was performed as a part of nationwide Japanese trials on post-operative adjuvant chemo-endocrine therapy for stage II and stage IIIa breast cancer with ftorafur (FT) alone and FT plus tamoxifen (TAM) and six districts.…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant therapy with chemotherapy and/or hormone therapy was decided according to nodal status and hormone receptor determination results. 15,16 All patients were followed-up every 3 months for 2 years, twice a year for the next year and then once a year. The median follow-up was 178 months (CI 95%: 174-183).…”
Section: Patientsmentioning
confidence: 99%
“…Each slice was put in as many separate cassettes as necessary and paraffin embedded. The median of blocks per patients was 3 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In total, 3 blocks per tumor were obtained in 68 cases (72%) and 4-17 blocks in 14 cases.…”
Section: Tissue Samples and Histological Examinationmentioning
confidence: 99%
“…Several controlled trials have been investigating the role of tamoxifen added to adjuvant chemotherapy in primary breast cancer (Bianco et al, 1988;Fisher et al, 1986;Fisher et al, 1981;Marshall et al, 1987;Mauriac et al, 1988;Tormey et al, 1990). The results of these trials have been confficting, most reporting a benefit of tamoxifen in receptor positive patients (Bianco et al, 1988;Fisher et al, 1986;Fisher et al, 1981;Marshall et al, 1987;Mauriac et al, 1988), while one trial found evidence of benefit in receptor negative patients only (Tormey et al, 1990 The patients were randomised into four groups:…”
mentioning
confidence: 99%
“…The results of these trials have been confficting, most reporting a benefit of tamoxifen in receptor positive patients (Bianco et al, 1988;Fisher et al, 1986;Fisher et al, 1981;Marshall et al, 1987;Mauriac et al, 1988), while one trial found evidence of benefit in receptor negative patients only (Tormey et al, 1990 The patients were randomised into four groups:…”
mentioning
confidence: 99%